Institution-Specific Perinatal Emergency Checklists: Multicenter Report on Development, Implementation, and Sustainability - Quist-Nelson, Johanna; Hannenberg, Alexander; Ruymann, Kathryn; Stover, Angela; Baxter, Jason K.; Smith, Stephen; Angle, Heidi; Gupta, Neeru; Lopez, Connie M.; Hunt, Eric; Tully, Kristin P. (American Journal of Perinatology, 2023)
Objective The American College of Obstetricians and Gynecologists and the Society for Maternal-Fetal Medicine endorse checklist use to improve obstetric care. However, there is limited research into development, implementation, and sustained use of perinatal emergency checklists to inform individual institutions. This study aimed to investigate the development and implementation of perinatal emergency checklists in diverse hospital settings in the United States.Study Design A qualitative study was conducted individually with clinicians from three health care systems. The participants developed and implemented institution-tailored perinatal emergency checklists. Interview transcriptions were coded using the Consolidated Framework for Implementation Research.Results The study sites included two health care systems and one individual hospital. Delivery volumes ranged from 3,500 to 48,000 deliveries a year. Interviews were conducted with all 10 participants approached. Checklists for 19 perinatal emergencies were developed at the three health care systems. Ten of the checklist topics were the same at all three institutions. Participants described the checklists as improving patient care during crises. The tools were viewed as opportunities to promote a shared mental model across clinical roles, to reduce redundancy and coordinate obstetric crisis management. Checklist were developed in small groups. Implementation was facilitated by those who developed the checklists. Participants agreed that simulation was essential for checklist refinement and effective use by response teams. Barriers to implementation included limited clinician availability. There was also an opportunity to strengthen integration of checklists workflow early in perinatal emergencies. Participants articulated that culture change took time, active practice, persistence, reinforcement, and process measurement.Conclusion This study outlines processes to develop, implement, and sustain perinatal emergency checklists at three institutions. Participants agreed that multiple, parallel implementation tactics created the culture shift for integration. The overview and specific Consolidated Framework for Implementation Research components may be used to inform adaptation and sustainability for others considering implementing perinatal emergency checklists.Key Points
Keywords: checklist; hemorrhage; perinatal emergencies; severe maternal morbidity; simulation; teamwork